Effects of Meditation Technique on Test Anxiety Among Secondary School Students in Anambra State, Nigeria - Nwokolo, Chinyelu; Blessing Mokwelu, Obianuju; Eva Eneasator, Uche (European Scientific Journal, ESJ, 2017)
Test anxiety constitutes a serious academic impediment to lots of students in schools. This study investigated the Effects of Meditation technique on test anxiety among secondary school students in Anambra State, Nigeria. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. Quasi-experimental research was adopted in carrying out the study. A sample size of 101 adolescents was chosen from a population of 475 adolescents in SS2 with test anxiety. The sample was derived from two schools selected using purposive sampling technique based on the number of students that scored high on Test Anxiety Inventory. Data relating to research questions were analysed using statistical Mean while data relating to hypothesis was analysed using Analysis of Covariance (ANCOVA). Findings from the study revealed among others that though the reduction of secondary school students’ test anxiety after meditation technique differed significantly with that of the conventional counselling group, meditation technique was not effective on secondary school students’ test anxiety. It further revealed that meditation technique reduced the secondary school students’ test anxiety. Based on the findings, implications of the study were noted and recommendations made that since the technique meditation was found not to be effective, but significantly reduced the test anxiety of the participants, the technique should not be used alone by the guidance counsellors in helping clients, especially students in overcoming their test anxiety in schools.